Estado plural y justicia para los "otros" pueblos: Crítica al modelo asimilador del estado-nación liberal clásico - Sánchez Torres, Augusto (2006)
Let us put our minds on the following social groups: some indigenous Aymara attending the judiciary, in which the judge and the other jurisprudents only speak Spanish; Quechua-speaking children who have to learn to read texts in Spanish, sent by the Ministry of Education from Lima; thousands of Andeans and Amazonians who have to suspend their work many days during the year -except Sundays-, well, the calendar marks a holiday for some «hero» -always military- some saint, or for the day of the Creole song.